Communicating the Baba-Nyonya cultural identity - Kuake, James Beng Mun (2010)
Baba-Nyonyas have been expressing their concern regarding maintaining the continuity of their cultural identity which is an important part of the Malaysian heritage today. They commonly express that their younger generation does not seem to be practicing the Baba-Nyonya cultural way of life. This study is to provide empirical evidence of the changing levels of demonstration of Baba-Nyonya way of life as manifested in the practice of Baba-Nyonya lifestyle, illustrated by the extent of material culture of this community as seen in their homes and possession of artifacts, and the quest of members of this community to identify themselves and taking pride in their being a Baba-Nyonya. A survey which returned 314 completed and usable questionnaires provided input from a spectrum of respondents representing generations of Baba-Nyonyas born from the 1920s through the 1990s, a span of seventy years. Respondents are delegates at the 21st Annual Baba-Nyonya Annual Convention held from 5th to 7th December 2008 in Melaka. Delegates are members of Penang, Melaka, Singapore and Kuala Lumpur local chapters of Baba-Nyonya associations who congregated annually, as they have been doing so for the past 21 years without interruption at their annual convention. Membership to local Baba-Nyonya associations require strict fulfillment of Baba-Nyonya bloodline and heritage. The demonstration of Baba-Nyonya cultural identity as represented by the three mentioned dimensions provided indication of how much the respondents desire to maintain and continue their heritage. This is manifested by their efforts and desire to invite, persuade, even compel their offspring to participate and “live up” to the Baba-Nyonya way of life i.e. communicating and transmitting cultural identity (enculturation). “Desire” to transmit their culture apply to respondents who during the data collection process do not have children at that point but extrapolated what they will do in the event they do have children. Pearson correlation indicated moderately positive and significant relationship between the demonstration of Baba-Nyonya cultural identity and the transmission of that culture. Multiple regression analysis indicated that the three dimensions of demonstration of Baba-Nyonya way of life contributed to 51 percent variance of enculturation efforts. The findings also indicated general decline in the demonstration of Baba-Nyonya cultural identity and efforts to transmit the culture but with a slight turnaround among respondents born in the 1990s. These can be explained by the broad and specific socio-economic and political scenarios surrounding these eras